DEVELOPMENT OF A METHODOLOGY FOR ASSESSING THE EFFICIENCY AND SAFETY OF INTERACTION OF THE CORPORATE AND FINANCIAL SECTOR IN THE CONDITIONS OF DIGITALIZATION - O. Chuvilova; L. Agarkova (Вестник Северо-Кавказского федерального университета, 2022)
Based on the identification of problems in assessing the effectiveness of interaction between the corporate and financial sectors of the economy in the context of digitalization, the article presents a qualitatively new methodology for assessing the safety and effectiveness of this interaction. The list of indicators included in the methodology at the micro and macro levels has been determined. The scale of solving the tasks is due to the fact that there are problems in the field of effective use of digital technologies to inance sustainable development of corporations, and ways to overcome them, in the possibility of a qualitative assessment. The presented methodology will simplify partnerships (including within ecosystems) in the context of digitalization.